Efficient Uranium Removal from Contaminated Water Using Laboratory-Prepared Zeolite - Odeh, Safana Saad; Al-Mashhadani, Asia H. (Iraqi Journal of Science, 2026)
Due to radioactive uranium pollution of water posing serious risks to human health and the environment, effective and sustainable cleanup techniques are required. Zeolite, a porous alumina-silicate mineral with a large surface area and ion-exchange capacity, has drawn interest as a successful uranium removal adsorbent. This study the removal of uranium from radioactively polluted water using laboratory prepared zeolite. To increase the adsorption efficiency, a number of variables were adjusted, such as pH, contact time, initial uranium content, and temperature. According to experimental studies, zeolite exhibits a great affinity for uranium ions and, in the right circumstances, can remove uranium ions with high efficiency. The results show that zeolite is an environmentally acceptable, inexpensive, and promising material for uranium decontamination in aquatic environments. By developing scalable techniques for treating radioactive wastewater, this research helps to ensure safer water supplies.